A game of losing control: weak subjectivity, questioning rationality and problematizing identification in narrative-based videogames - Sterczewski, Piotr (Replay. The Polish Journal of Game Studies, 2014)
The article diagnoses prevalent tendencies in game design and styles of play, positioning players as strong, active, rational, and extraordinary characters able to change the world around them; embodying the logic of inevitable linear progress both in story and game mechanics; encouraging players to optimize their actions to achieve measurable gameplay effects. Foucault’s notion of technologies of the self is used to highlight personal identification with the playable character as a predominant style of play in narrative-based videogames. The article then examines the examples of games that challenge these established tendencies – where the playable character’s intent is made impossible to achieve, rationality of playable character is questioned, the player gets deprived of control of their character in key moments of the game or the identification with the character becomes problematized. The phenomenon is exemplified by the games Spec Ops: The Line, Heavy Rain, Actual Sunlight and The Witcher series.